Case study: customers satisfaction towards Mercedes-Benz’s after sales & services / Fazli Shah Simpon - Simpon, Fazli Shah (Faculty of Business and Management, 2010)
Customer satisfaction towards the level of service in product and service base business had been taking into deeper understanding in the recent years to improve the company’s performance and to understand the critical areas in consumer’s minds towards which factors contributes to a good service. This case study focuses on identifying the level of customer satisfaction towards After Sales and Services provided by Mercedes-Benz Malaysia. Service business always encountered problems of service effectiveness, quality of service and how to increase the productivity from time to time. Taking the customer’s points of view and opinions from the experts from Mercedes- Benz Malaysia, this study hoping to understand what is the level of customer satisfaction towards Mercedes-Benz Malaysia, how to create the awareness for the service provider on the importance of understanding the customer’s policy and standard, consequently learning to improve the level of satisfaction of the Mercedes- Benz’s customers.